2021
DOI: 10.1123/ijspp.2019-1001
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Capacity According to Playing Role and Position in Elite Female Basketball Players Using Laboratory and Field Tests

Abstract: Purpose: To compare the aerobic capacity of elite female basketball players between playing roles and positions determined using maximal laboratory and field tests. Methods: Elite female basketball players from the National Croatian League were grouped according to playing role (starter: n = 8; bench: n = 12) and position (backcourt: n = 11; frontcourt: n = 9). All 20 players completed 2 maximal exercise tests in a crossover fashion 7 days apart. First, the players underwent a laboratory-based continuous runni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Aerobic capacity development is warranted to facilitate recovery between bouts of high-intensity activity while minimizing the physiological response to fatigue (42,66,69). More specifically, guards and starting players should attain the highest aerobic capacity levels to sustain optimal levels of play (87). A commonly used method of improving aerobic capacity levels includes shortsided conditioning games.…”
Section: Bioenergetic Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Aerobic capacity development is warranted to facilitate recovery between bouts of high-intensity activity while minimizing the physiological response to fatigue (42,66,69). More specifically, guards and starting players should attain the highest aerobic capacity levels to sustain optimal levels of play (87). A commonly used method of improving aerobic capacity levels includes shortsided conditioning games.…”
Section: Bioenergetic Developmentmentioning
confidence: 99%
“…Appropriate considerations should be given to exercise selection, volume, intensity, and total volume-load. Thought should be given to how the preceding variables can be manipulated to improve or maintain strength, increase individual peak and maximal power, decrease injury risk, and concurrently improve player readiness through daily and weekly fatigue monitoring assessments (55,87,106).…”
Section: Factors Affecting Muscular Strength and Power Developmentmentioning
confidence: 99%
“…1 Although basketball is thought to be mainly dependent on players’ anaerobic capacity, high aerobic capacity is also crucial for improving performance. 2 Aerobic capacity is related to the frequency of high-intensity activities and the distance covered at maximal-speed running during basketball games. 3 Moreover, there are several other factors influencing the competitive performance, such as technical and tactical skills.…”
Section: Introductionmentioning
confidence: 99%
“…For athletes competing in seasonal sport, it has been suggested that players who train once or twice a week and play minimal minutes in matches might not receive sufficient stimuli to maintain adequate conditioning in-season (Joyce and Lewindon, 2014 ). Additionally, starting players have been reported to possess superior aerobic conditioning when compared to bench players (Scanlan et al, 2021 ), which is potentially caused or amplified by the extra in-game conditioning starting players receive compared to bench players (Palmer et al, 2021 ; Russell et al, 2021 ). Therefore, bench players out of the main rotation who receive reduced playing time during a finals series might need to supplement their conditioning training during finals with extra maximal and supramaximal-intensity activity to ensure their conditioning levels are not further reduced compared to starters (Joyce and Lewindon, 2014 ).…”
Section: Discussionmentioning
confidence: 99%